Ötz-T: 3D-printed open-source turbidity sensor with Arduino shield for suspended sediment monitoring. (March 2023) - Droujko, Jessica; Kunz Jr, Felix; Molnar, Peter
Graphical abstract: Abstract: Fine sediment production in catchments and transport through rivers to floodplains and coastal areas is extremely important for riverine, coastal and marine ecosystems, nutrient transport, global biogeochemical cycles, water quality and pollution. Due to the high cost of suspended sediment monitoring technology, it is extremely difficult to obtain a complete understanding of the physical connections between climate, hydrology, fluvial processes, and sediment fluxes, which requires measurements at many locations. For this reason, we have built an open-source turbidity sensor that brings accessibility to global river research. Compared to commercial turbidity sensors ( > 6000€), our low-cost version ( ∼ 200€) allows for multiple deployment and therefore a high spatial coverage of sediment fluxes. It is an optical scatter sensor with an 850 nm LED and two IR detectors, and features a temperature and pressure sensor. Our sensor is 3D-printed on a hobby printer and is programmed with Arduino IDE, making it accessible to those without high-tech workshop access and limited programming skills. It features a printed circuit board that stacks on top of an ultra low-power Arduino MKR WAN 1310, for durability and easy assembly. The sensor was tested during a flood in September 2022 on the Ötztal Ache in Tirol, Austria.